Strategies of Cultural Integration in Successful Merger-Companies - Achmad Supriyanto; Burhanuddin Burhanuddin (Universitas Negeri Malang, 2019)
Abstract: This research aimed to discover strategies in integrating a new culture within the merger companies. The strategies have elements including values, phases, leader role, and the system of cultural integration construction. This research used a meta-analysis with an expose facto research design. Findings indicate new cultural integrations were carried out by many companies through demonstrating internal and external values. Integrations are implemented through 'pre, process, and post-merger'.  The most important in the preliminary stage is started by benchmarking, leading entire stages, and keeping a balance of collaboration between human and non-human aspects as well as leader and member components. This study concludes that the identified strategies highly contributed to effective management changes at micro, meso, and macro level. The implication is that leaders have to consider new cultural integration strategies properly. Since this study were based on meta analysis findings, future research needs to include empirical data originated from merging organizations. Key Words: strategy, cultural integration, organization Abstrak: Penelitian ini bertujuan untuk menemukan strategi guna mengintegrasikan budaya baru dalam perusahaan merger. Dalam elemen strategi terdapat nilai-nilai, fase, peran pemimpin, dan sistem konstruksi integrasi budaya. Penelitian ini menggunakan meta-analisis dengan desain expose facto. Temuan dari banyak perusahaan melalui pembuktian nilai-nilai internal dan eksternal. Integrasi dilaksanakan melalui 'pra, proses, dan pasca merger'. Dalam tahap pendahuluan, hal yang paling penting adalah benchmarking, memimpin seluruh tahapan, dan menjaga keseimbangan antara kolaborasi dan aspek non-manusia serta komponen pemimpin dan anggota. Studi ini menyimpulkan bahwa strategi sangat berkontribusi terhadap perubahan manajemen yang efektif di tingkat mikro, mezo, dan makro. Para pemimpin harus mempertimbangkan strategi integrasi budaya baru dengan benar. Penelitian masa depan perlu memasukkan data empiris yang berasal dari penggabungan organisasi. Kata kunci: strategi, integrasi budaya, organisasi